Analisis Yuridis Pengaturan Sanksi Bagi Penolak Vaksinasi Covid-19 - Sigalingging, Yulia Emma; Santoso, Aris Prio Agus (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
Referring to Article 28H paragraph (1) of the 1945 Constitution, the Government has tried to ensure the health of its citizens through the Covid-19 Vaccination program, but there are still people who refuse to be given the Covid-19 vaccination, and this has become a pro and con in the community. The formulation of the problem in this study is how to set sanctions for refusal of Covid-19 vaccination and how the right to refuse the Covid-19 vaccination is viewed from the point of view of Human Rights. This research method uses a normative juridical approach, with data collection from literature studies. The data obtained were analyzed qualitatively. Based on the results of the study, it was found that the sanctions for refusing the Covid-19 vaccine were in the form of imprisonment of 6 months to 1 year in prison or a fine of Rp. 500,000 - Rp. 1,000,000. In addition, there are sanctions in the form of delaying or discontinuing the provision of social security or social assistance, delaying or discontinuing government administrative services, and fines. In fact, refusing to be vaccinated against Covid-19 is a form of individual freedom that cannot be forced with all considerations to express his aspirations regarding the risks and consequences to his body. Where this should be respected by the Government as stated in Article 28J Paragraph (1) of the 1945 Constitution